BISNIS DAYCARE DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS DI DAYCARE SAHABAT TELADAN) - Suprapto , Umar; Saftarijan , Helmi (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2024)
The aim of this research was regarding the implementation of daycare, the view of Islamic law and a comprehensive view of Islam regarding the daycare business, one of which is the Sahabat Teladan daycare. The method used in the research is a qualitative method. Based on research results, Sahabat Teladan daycare has a monthly and daily service system with full day, half day and weekend. The reason parents entrust their children to daycare is because there are no relatives who can look after them and hope that the child's growth and development will be better. Intrinsic motives are more dominant as the reason why parents choose daycare. Apart from that, the existence of daycare is perceived to be very helpful to the needs/difficulties of parents in caring for and educating children, and the daycare is considered trustworthy, open to criticism and suggestions, the costs incurred are in accordance with the facilities and services obtained, caretakers do not act rudely in caregiving and education. . According to Islamic views, daycare business law is permissible or permissible, unless there is an element of docility then it will become haram.